2010
DOI: 10.4137/ijtr.s3804
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Tryptophan, 5-Hydroxytryptophan and Serotonin in Patients Affected with Different Forms of Amenorrhea

Abstract: Tryptophan (Trp) is present in the serum, partly bound to albumine and in the free form. The unbound portion of circulating tryptophan has the property of crossing the hematoencephalic barrier and being converted within the brain into serotonin (5-HT) through the enzymatic processes of hydroxylation and decarboxylation. The serotoninergic system plays an important role in neuroendocrine control of reproductive hormone secretion, and in particular, it may influence GnRH pulsatility, a function essential for rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 16 publications
1
18
1
Order By: Relevance
“…Tryptophan amino acid in seronegative leprosy was slightly lower than other study conducted in Poland [16]. Tryptophan amino acid is an essential amino acid which important not only for the host but also bacteria.…”
Section: Discussioncontrasting
confidence: 54%
“…Tryptophan amino acid in seronegative leprosy was slightly lower than other study conducted in Poland [16]. Tryptophan amino acid is an essential amino acid which important not only for the host but also bacteria.…”
Section: Discussioncontrasting
confidence: 54%
“…As can be seen, some substances, such as captoprit, tryptophan and copper(II), interfered with the CL signal. However, their interferences would be a small and neglectable one, since their concentrations are less than one‐tenth of the cysteine concentration in human serum . It was also observed that ascorbic acid interfered with the cysteine determination, and needs to be removed.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggested that these two enzymes differ from each other in their preference for L-tryptophan analogs. Nevertheless these reactivities toward 5-hydroxy-L-tryptophan are unlikely to affect the accuracy of the L-tryptophan measurement in blood because the 5-hydroxy-L-tryptophan concentration is less than 1% that of the L-tryptophan concentration in blood [42].…”
Section: Substrate Specificity Of Stao and Vioamentioning
confidence: 99%